Programming C♯ 3.0 - Liberty, Jesse (O'Reilly, 2008)
Explores the key concepts of C♯ 3.0, the features of .NET 3.5 to access and work with data, ways to use C♯ with the Microsoft frameworks to build applications, and how to use the .NET CLR to deploy and manage data.